Penegakan Hukum sebagai Percepatan Pengamanan Lahan IKN Guna Meminimalisir Potensi Konflik di Kawasan Inti Pusat Pemerintahan (IPP) dalam Rangka Keamanan Nasional - Tetty Melina Lubis; Tiarsen Buaton; Arief Fahmi Lubis; Parluhutan Sagala (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This article discusses the importance of law enforcement in accelerating the security of IKN (State Capital) land to minimize potential conflicts in the Central Government Core Area (IPP). Effective law enforcement can help prevent conflicts and ensure national security. This article explores the role of law enforcement in securing IKN land and how this can contribute to national security.